Costs of using evidence‐based implementation strategies for behavioral health integration in a large primary care system. (30th November 2020) - Yeung, Kai; Richards, Julie; Goemer, Eric; Lozano, Paula; Lapham, Gwen; Williams, Emily; Glass, Joseph; Lee, Amy; Achtmeyer, Carol; Caldeiro, Ryan; Parrish, Rebecca; Bradley, Katharine
Abstract: Objective: To describe the cost of using evidence‐based implementation strategies for sustained behavioral health integration (BHI) involving population‐based screening, assessment, and identification at 25 primary care sites of Kaiser Permanente Washington (2015‐2018). Data Sources/Study Setting: Project records, surveys, Bureau of Labor Statistics compensation data. Study Design: Labor and nonlabor costs incurred by three implementation strategies: practice coaching, electronic health records clinical decision support, and performance feedback. Data Collection/Extraction Methods: Personnel time spent on these strategies was estimated for five broad roles: (a) project leaders and administrative support, (b) practice coaches, (c) clinical decision support programmers, (d) performance metric programmers, and (e) primary care local implementation team members. Principal Finding: Implementation involved 286 persons, 18 131 person‐hours, costing $1 587 139 or $5 per primary care visit with screening or $38 per primary care visit identifying depression, suicidal thoughts and/or alcohol or substance use disorders, in a single year. The majority of person‐hours was devoted to project leadership (35%) and practice coaches (34%), and 36% of costs were for the first three sites. Conclusions: When spread across patients screened in a single year, BHI implementation costs were well within the range for commonly used diagnostic assessments in primary care (eg, laboratory tests). This suggests that implementation costs alone should not be a substantial barrier to population‐based BHI.